2004
DOI: 10.1210/me.2003-0366
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Glucocorticoid Receptor-Mediated Gene Expression by Constitutively Active Heat Shock Factor 1

Abstract: To further define the role of heat shock factor 1 (HSF1) in the stress potentiation of glucocorticoid receptor (GR) activity, we placed a constitutively active mutant of human HSF1 (hHSF1-E189) under the control of a doxycycline (DOX)-inducible vector. In mouse L929 cells, DOX-induced expression of hHSF1-E189 correlated with in vivo occupancy of the human heat shock protein 70 (hHsp70) promoter (chromatin-immunoprecipitation assay) and with increased activity under nonstress conditions at the hHsp70 promoter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…In this respect, Wadekar et al (2001) showed that glucocorticoids can suppress the heat shock response in cells by inhibiting the actions of heat shock factor 1 (HSF1). In stressed cells, activation of GR signaling causes rapid inactivation of HSF1 by blocking its actions at the promoter of Hsp70 and probably other Hsp genes (Jones et al, 2004). Interestingly, the indel (AA) was completely linked to the C-G transversion at position À 660 reported by MarcosCarcavilla et al (2010b), which was also found in all breeds here analyzed.…”
Section: Resultssupporting
confidence: 69%
“…In this respect, Wadekar et al (2001) showed that glucocorticoids can suppress the heat shock response in cells by inhibiting the actions of heat shock factor 1 (HSF1). In stressed cells, activation of GR signaling causes rapid inactivation of HSF1 by blocking its actions at the promoter of Hsp70 and probably other Hsp genes (Jones et al, 2004). Interestingly, the indel (AA) was completely linked to the C-G transversion at position À 660 reported by MarcosCarcavilla et al (2010b), which was also found in all breeds here analyzed.…”
Section: Resultssupporting
confidence: 69%
“…Overexpression of FoxM1 and Constitutively Active HSF1-Hs683 cells were transfected with FoxM1 expression plasmid pcDNA3-FoxM1, CMV-hHSF1 (ϩ) (constitutively active HSF1 plasmid), CMV-hHSF1 (Ϫ) (non-active HSF1 plasmid) (34), and control vector using Lipofectamine 2000. Expression of transfected genes was confirmed with Western blotting, and the FoxM1-transfected cells were treated with heat shock stress followed by cell cycle analysis.…”
Section: Methodsmentioning
confidence: 99%
“…5F). Most of the other motifs positively predictive for enhancer activation were for factors that have been shown to participate with GR in genomic binding and/or transcriptional activation (e.g., HSF [Jones et al 2004]; CEBP [Steger et al 2010]; RAR/RXR [Tóth et al 2011]; VDR ; TEAD and FOX [Starick et al 2015]). Thus, these factors may act in concert with GR, given the widespread direct binding of GR in activated enhancers.…”
Section: Cold Spring Harbor Laboratory Press On March 29 2019 -Publimentioning
confidence: 99%